2012
DOI: 10.1186/1471-2377-12-63
|View full text |Cite
|
Sign up to set email alerts
|

Acute posthypoxic myoclonus after cardiopulmonary resuscitation

Abstract: BackgroundAcute posthypoxic myoclonus (PHM) can occur in patients admitted after cardiopulmonary resuscitation (CPR) and is considered to have a poor prognosis. The origin can be cortical and/or subcortical and this might be an important determinant for treatment options and prognosis. The aim of the study was to investigate whether acute PHM originates from cortical or subcortical structures, using somatosensory evoked potential (SEP) and electroencephalogram (EEG).MethodsPatients with acute PHM (focal myoclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
124
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(135 citation statements)
references
References 30 publications
7
124
1
3
Order By: Relevance
“…Moreover, in this cohort CM was more likely present in patients with generalized PHM than in focal PHM. This result is in line with earlier studies who demonstrated that generalized PHM can arise from the cortex 5, 6, 33. These findings suggest that the clinical model of typical CM and SM phenomenology that physicians encounter in noncomatose myoclonus patients at the outpatient clinic does not apply for PHM in the first few days after resuscitation 10, 11.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Moreover, in this cohort CM was more likely present in patients with generalized PHM than in focal PHM. This result is in line with earlier studies who demonstrated that generalized PHM can arise from the cortex 5, 6, 33. These findings suggest that the clinical model of typical CM and SM phenomenology that physicians encounter in noncomatose myoclonus patients at the outpatient clinic does not apply for PHM in the first few days after resuscitation 10, 11.…”
Section: Discussionsupporting
confidence: 91%
“…This finding suggests that patients with a multiple lesioned cortex (and CM) could have a worse outcome compared to patients with a singular, small brainstem lesion (and SM). In addition, studies that correlated the generalized and focal PHM phenotype to outcome found that the severity of myoclonus, and not per se the presence or absence of brainstem damage, was related to poor outcome 1, 5, 6. Yet in contrast, another finding of this study was that in patients presenting PHM within 24 h after CPR, significantly less CM occurred (Table 3).…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…The current hot topic in resuscitation is prog nostication. This field is moving rapidly, largely because of the accumulating evi dence that therapeutic hypothermia modi fies the recovery process in the comatose post cardiac arrest patient-we have un doubtedly been making withdrawal deci sions far too early in these patients [30,31]. The Swedish Resuscitation Council has al ready published updated guidelines on neurological prognostication after cardiac arrest [32] and I expect that other organi sations will publish guidance over the next few months.…”
Section: The International Liaison Committee On Resuscitation (Ilcor)mentioning
confidence: 99%